The role of agricultural extension services in promoting agricultural sustainability: a Central Malawi case study - Leah M. Mungai; Joseph P. Messina; Leo C. Zulu; Regis Chikowo; Sieglinde S. Snapp (Cogent Food & Agriculture)
This study examines the experiences of personnel in the agricultural extension system, aiming to understand the multifaceted nature, challenges, and opportunities of extension service delivery from their perspective. Using a snowball sampling approach, we conducted semi-structured interviews with 19 purposively selected extension staff from four Extension Planning Areas (EPAs) sites in central Malawi. Thematic analysis was utilized to identify key themes, including agricultural practices, land and water management, and livestock production, as well as extension training approaches and information sources. Findings revealed a diverse extension service provided by various actors, including government agencies, non-government organizations, farmer groups, and the private sector. All participants mentioned using the Guide to Agricultural Production booklet, the official manual for agricultural information, along with printed leaflets (79%) containing specific technologies from crop specialists. Advisory topics covered were crop and soil management, land, and climate-smart practices, primarily disseminated through the lead farmer system (84%) and farmer field schools (47%). Additionally, recent mobile technologies such as WhatsApp and traditional radio, which offer the widest geographic coverage, were identified by some participants as key channels for information communication. This study identified potential new areas for enhancing extension services. These include: (a) fostering multidirectional engagement through partnerships among public, private, and non-governmental extension services, alongside farmer-group participation platforms (b) expanding the scope of extension advisory service and training to address urgent issues such as climate change adaptation and value addition, and (c) integrating mobile phone and media innovations to address the low extensionist-farmer ratio problem and bridge information and service gaps.